2017
DOI: 10.1002/aic.15756
|View full text |Cite
|
Sign up to set email alerts
|

More active Ir subnanometer clusters than single‐atoms for catalytic oxidation of CO at low temperature

Abstract: This work reported the adsorption and reaction performance of FeOx supported subnanometer cluster and single‐atom Ir catalysts for the oxidation of CO at low temperature. By varying the pretreatment temperature and Ir loading, the single‐atom and subnanometer cluster Ir catalysts were obtained. The Ir subnanometer clusters exhibited higher activity for the oxidation of CO with or without the presence of H2 than the single‐atom counterpart. By using adsorption microcalorimetry and in situ infrared spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 71 publications
1
44
0
Order By: Relevance
“…In connection to these findings, the superiority of subnanometric clusters overs single atoms was previously reported for CO oxidation over Ir/FeOx. 46…”
Section: Resultsmentioning
confidence: 99%
“…In connection to these findings, the superiority of subnanometric clusters overs single atoms was previously reported for CO oxidation over Ir/FeOx. 46…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al used infrared to observe the adsorption of CO on single atomic Ir and sub‐nano Ir clusters. It was found that Ir had an absorption peak only at 2043 cm −1 , which proved the existence of Ir single atoms . In addition, the structural characteristics of the atoms in several angstrom scales can be further obtained by Fourier transforming the X‐ray absorption spectrum .…”
Section: Typical Characterization Of Nonprecious Metal Single Atomic mentioning
confidence: 99%
“…c) Infrared adsorption of CO on 2.4Ir/Fe‐UC‐ x . Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Typical Characterization Of Nonprecious Metal Single Atomic mentioning
confidence: 99%
“…However, it's also well known that aimlessly and endlessly downsizing the metal particles does not necessarily guarantee a better catalytic performance. [8][9][10][11][12][13][14][15] The so-called "size effect" is too simplied to explain various phenomena that have been experimentally observed in different catalytic reactions by all sorts of SACs. In addition, not only does the single atom matter in reactions, but the environment including the oxide support and the metal-support interaction also plays a critical role in the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%